2004
DOI: 10.1038/sj.embor.7400171
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of germline transgenic chickens using lentiviral vectors

Abstract: An effective method for genetic modification of chickens has yet to be developed. An efficient technology, enabling production of transgenic birds at high frequency and with reliable expression of transgenes, will have many applications, both in basic research and in biotechnology. We investigated the efficiency with which lentiviral vectors could transduce the chicken germ line and examined the expression of introduced reporter transgenes. Ten founder cockerels transmitted the vector to between 4% and 45% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
274
5
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(300 citation statements)
references
References 23 publications
6
274
5
8
Order By: Relevance
“…Lentiviral vectors have also been used to generate transgenic pigs and cattle (8,9), and, in principle, they should allow for the generation of transgenic birds. Indeed, promising results were obtained in chickens with the use of recombinant equine infectious anemia virus (EIAV), a type of lentivirus (10). Transgenic chickens were generated that expressed GFP in some tissues; however, the pattern of GFP expression was inconsistent with the expected activity of the viral promoter used.…”
mentioning
confidence: 99%
“…Lentiviral vectors have also been used to generate transgenic pigs and cattle (8,9), and, in principle, they should allow for the generation of transgenic birds. Indeed, promising results were obtained in chickens with the use of recombinant equine infectious anemia virus (EIAV), a type of lentivirus (10). Transgenic chickens were generated that expressed GFP in some tissues; however, the pattern of GFP expression was inconsistent with the expected activity of the viral promoter used.…”
mentioning
confidence: 99%
“…Lentiviral vectors are also suitable to create genetically modified birds. Transgenic chicken stably expressed a reporter gene up to the F2 generation (McGrew et al, 2004), and tissue-specific expression in birds was reported in quails, where Scott et al demonstrated that the use of a GFP vector, driven by the human synapsin gene I promoter lead to the expression of GFP in neurons, which was persistent across multiple generations (Scott and Lois, 2005).…”
Section: Lentiviruses Have Been Isolated From Sheep (Visna/maedi Virumentioning
confidence: 99%
“…Recent publications have shown that lentiviral vectors are highly efficient for the generation of transgenic mammals (for review see ), such as mouse (Lois et al, 2002a;Pfeifer et al, 2002), rat (Nakagawa et al, 2005), pig (Hofmann, et al 2003 ), cattle (Hofmann et al, 2003;Hofmann et al, 2004) and chicken (McGrew et al, 2004). In our previous studies, we used HIV-1 based lentiviral vectors which contain a self-inactivating (SIN) mutation for the generation of transgenic pigs and cattle (Hofmann et al, 2003a;Hofmann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These vectors have proven highly efficient in generating transgenic mice [4], pigs [5], cows [6], chickens [7,8] and sheep [9].…”
Section: Use Of Retroviral Vectorsmentioning
confidence: 99%